Delägarna i Snefringe Häradsallmänning - synen på skogens värden - Martin, Viktorsson (2019)
The present study focused on the shareholders (one share equals one mantal in Swedish) among Snefringe häradsallmänning. Snefringe is most easily described as a privately-owned community forest that conducts active forestry. Snefringes present land holdings is approximately 7 800 hectares and the number of shareholders is approximately 540.